2009
DOI: 10.1002/ijc.24522
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐10b is overexpressed in malignant glioma and associated with tumor invasive factors, uPAR and RhoC

Abstract: MicroRNAs (miRNAs) are effective post-transcriptional regulators of gene expression and are important in many biological processes. Although the oncogenic and tumor suppressive functions of several miRNAs have been characterized, the role of miRNAs in mediating tumor invasion and migration remains largely unexplored. Recently, miR-10b was identified as an miRNA highly expressed in metastatic breast cancer, promoting cell migration and invasion. Here, we performed real-time reverse transcriptase polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
219
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(231 citation statements)
references
References 29 publications
8
219
1
3
Order By: Relevance
“…Although there was no significant difference in miR-195 levels between the healthy control and breast cancer, both miR-362-3p and miR-329 showed lower expression levels in tumors compared with the matching control tissues (Figure 4b). In line with other reports showing downregulation of miR-329 in neuroblastoma and glioma, [20][21][22] we found that both miR-362-3p and miR-329 were significantly downregulated in human breast cancer tissues. To confirm the observed change of miRs expression in individual patients, we processed small-RNA expression data of estrogen receptor-positive (ER-positive) patient samples from the cancer genome atlas (TCGA).…”
supporting
confidence: 93%
“…Although there was no significant difference in miR-195 levels between the healthy control and breast cancer, both miR-362-3p and miR-329 showed lower expression levels in tumors compared with the matching control tissues (Figure 4b). In line with other reports showing downregulation of miR-329 in neuroblastoma and glioma, [20][21][22] we found that both miR-362-3p and miR-329 were significantly downregulated in human breast cancer tissues. To confirm the observed change of miRs expression in individual patients, we processed small-RNA expression data of estrogen receptor-positive (ER-positive) patient samples from the cancer genome atlas (TCGA).…”
supporting
confidence: 93%
“…Overexpression of miR-10b in otherwise nonmetastatic breast tumors initiated robust invasion and metastasis [8]. miR-10b is a unique miRNA expressed specifically in glioma tumors but not in normal brain cells: neither neural progenitor cells nor mature glia or neurons [9,10]. It has been reported that miR-10b was upregulated in all glioma samples compared with nonneoplastic brain tissues; the expression level of miR-10b was associated with higher-grade glioma and the tumor invasive factors uPAR and RhoC [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies subsequently found increased expression of miR-10b to be associated with aggressive behavior in various cancers. [34][35][36][37][38] In melanoma, miR-10b was identified in miRNA discovery studies 9,39 but no studies have focused on miR-10b as the primary melanoma candidate biomarker. Segura et al 9 conducted a discovery analysis in melanoma and miR-10b was associated with increased post-recurrence survival, which contradicts our findings.…”
Section: Discussionmentioning
confidence: 99%